2014
DOI: 10.1097/01.pra.0000454780.59859.9e
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Treatment Utilization by Hospitalized Suicidal Adolescents

Abstract: This study examines treatment utilization in a sample of 99 adolescents who were psychiatrically hospitalized due to a risk of suicide and followed for 6 months. Descriptive information regarding participants’ use of various forms of outpatient and intensive treatment, including emergency, inpatient, and residential care is presented. In addition, the relationships between utilization of mental health services and various characteristics of the adolescents and their families were assessed. Overall treatment en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 23 publications
1
26
1
Order By: Relevance
“…Other reports based on this sample have been published elsewhere (Selby, & Yen, 2014; Yen, Fuller, Solomon, & Spirito, 2014; Yen, Gagnon, & Spirito, 2013; Yen, Kuehn, et al, in press; Yen et al, 2012). The present study differs from those studies in that here we examine predictors of NSSI using the Functional Assessment of Self-Mutilation (FASM).…”
Section: Methodsmentioning
confidence: 91%
“…Other reports based on this sample have been published elsewhere (Selby, & Yen, 2014; Yen, Fuller, Solomon, & Spirito, 2014; Yen, Gagnon, & Spirito, 2013; Yen, Kuehn, et al, in press; Yen et al, 2012). The present study differs from those studies in that here we examine predictors of NSSI using the Functional Assessment of Self-Mutilation (FASM).…”
Section: Methodsmentioning
confidence: 91%
“…19% of adolescents in total attempted suicide anew in the monitored six-month period. The authors declare that patients who were psychiatrically hospitalized after attempted suicide require longer psychiatric hospitalization, better planning of passage from hospitalization to outpatient care and more intensive outpatient care (34).…”
Section: Discussionmentioning
confidence: 99%
“…This could influence follow-up on both the patient and provider side, which is consistent with the hypothesis that those with more severe illnesses are more likely to follow-up. 20 However, we observed that longer length of stay reduces the likelihood of follow-up, which may be counterintuitive to the severity hypothesis and require future investigation. For example, analyses with greater numbers of hospitalizations than we observed could parse out complex interactions between diagnosed conditions and the hospital length of stay.…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have consistently observed lower-than-optimal rates of follow-up among individuals, but comparisons are difficult to interpret given differences in populations by age, diagnosis, health insurance coverage (ie, Medicaid, private, etc), and inconsistent follow-up care specifications. [10][11][12][14][15][16][17]19,20 National performance on this measure is highly variable, and comparability across states and programs is difficult to ascertain. 21,22 Differences between Medicaid and CHIP notwithstanding, some state CHIPs report only on fee-for-service enrollees, whereas others include managed care or specific administrative subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation